QoS improvement for multimedia traffic in WLANs with TTN approach - Seeme, Fatima Bilkis; Arafat, Abdullah Omar; Dimyati, Kaharudin (Academic Journals, 2010)
This study proposes a Time Division Multiple Access (TDMA) based token passing MAC (Media Access Control) protocol, TTN (TDMA based Token Network). In the proposed scheme, the Access Point (AP) assigns time slot to the stations and passes on a token. The stations are allowed to transmit only when they get hold of the token. Through simulation study, it is shown that TTN can perform better in case of throughput, delay performance compared to EDCA (Enhanced Distributed Channel Access) based 802.11e. So TTN can support more real-time traffic streams with satisfactory QoS level.